A New Comprehensive Approach for Health Promotion Initiatives in Thailand: an Overview of Steps for Funding, Research, Implementation, and Outcome Measurement - ศรไพศาล, บัณฑิต; Rehm, Jürgen (Journal of Health Science of Thailand, 2020)
Health promotion efforts are crucial in Thailand to increase the overall well-being of the Thai people, to prevent and control non-communicable diseases, and ultimately to achieve the Sustainable Development Goals. A new, comprehensive, and stepwise approach to promote the health of the Thai people is proposed. This conceptual framework provides a step-by-step, “how-to” guide which covers everything from funding, to research strategies, to implementation of initiatives, and finally to outcome measures. Its goal is to serve as a guide that Thai citizens and various coalitions can adopt in order to collectively execute health promotion strategies and activities aimed at improving the health of the Thai people. This approach consists of seven steps. The first is the foundation step, which includes the creation of effective funding management and governance systems and fundamental supporting mechanisms, such as health promotion monitoring and evaluation systems. The second is the research step, used to generate knowledge and model development. The third is the persuasion step, which includes policy advocacy, media advocacy, and strategic networking for health promotion activities. The fourth is the adoption step, which involves the decision-making process around implementing effective health promotion strategies and activities. The fifth is the systematic implementation step required for health promotion strategies and activities. The sixth step identifies changes in health behaviours and healthy environments. The seventh step is the health outcomes step, used to measure changes in morbidity, mortality and well-being of the Thai people. This new systematic approach will synergize all stakeholder efforts towards health promotion in Thailand, with the aim of achieving better health for all Thai people, and eventually achieving the Sustainable Development Goals.